SEBARAN DAN KEPADATAN BURUNG TEKUKUR DI PULAU KISAR KABUPATEN MALUKU BARAT DAYA KECAMATAN KISAR UTARA - Ona Cornelis; Ali Awan (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Birds are part of biodiversity that must be preserved from extinction and decrease in species diversity. This study aims to determine the density and distribution of Tekukur birds in the North of Lebelau, Nomaha and Purpura Villages, Kisar District, Southwest Maluku Regency. Method: This study used a descriptive survey method in three locations namely Lebelau, Nomaha and Purpura Villages. At each research location taken in the plantation area, bushes and trees. Result: Based on the research that has been done in Lebelau, Nomaha and Purpura villages, the density values ​​range between 76.6 ind / KM²-96.6 ind / KM, which shows that the highest density is in Lebelau village with a density value of 96.6 ind / KM², and the lowest is in Purpura Village with a density of 76.6 ind / KM², Conclusion: Distribution patterns in Lebelau, Pupura and Nomaha Villages include evenly distributed distribution patterns.